2009
DOI: 10.1557/jmr.2009.0318
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing effects of carbon nanotubes in structural aluminum matrix nanocomposites

Abstract: The reinforcing effects of carbon nanotubes (CNTs) are investigated for aluminum matrix composites. The composites present a strong bonding between CNTs and the aluminum matrix using a controlled mechanical milling process, producing a network structure of aluminum atoms around CNTs. At the same time, CNTs that are dispersed during the milling process can be located inside aluminum powders, thereby providing an easy consolidation route via thermomechanical processes. A composite containing 4.5 vol% multiwalled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(72 citation statements)
references
References 15 publications
0
66
0
3
Order By: Relevance
“…The enhancement of flow curves in the composite compared with the base alloy was also observed at all test temperatures at a fixed strain rate ( Fig.8(b)), indicating the importance of CNT reinforcement in the improvement of the mechanical properties. Similarly, Choi et al [54] also observed the improvement in the flow resistance by the addition of CNTs while studying composites with different volume fractions of MWCNTs (i.e., 1.5, 3, 4.5 and 6 vol.%) at different temperatures. The evaluated CYS and UCS are shown in Fig.10.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 81%
“…The enhancement of flow curves in the composite compared with the base alloy was also observed at all test temperatures at a fixed strain rate ( Fig.8(b)), indicating the importance of CNT reinforcement in the improvement of the mechanical properties. Similarly, Choi et al [54] also observed the improvement in the flow resistance by the addition of CNTs while studying composites with different volume fractions of MWCNTs (i.e., 1.5, 3, 4.5 and 6 vol.%) at different temperatures. The evaluated CYS and UCS are shown in Fig.10.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 81%
“…Flaky Al particles with greatly improved surface areas have been reported in high-energy ball milling (HEBM) processes by preventing cold-welding of Al powders [10,16]. However, due to the ignorance of the strong attractive force between CNTs HEBM process also confronted the severe CNT damages for dispersing CNTs [17]. Accordingly, homogeneous CNT dispersion with minor or small structure change in composites is difficult to obtain from the conventional methods based on a single-aspect strategy.…”
Section: Introductionmentioning
confidence: 99%
“…While few materials in their elemental form can meet these requirements, the development of nanostructure-reinforced metal matrix composites (MMCs) has opened new pathways for the design of new materials that exhibit a unique set of properties, such as high strength and low weight. The performance of MMCs depends primarily on the ability (1) to adequately disperse the reinforcement agents in the metal matrix, (2) to maintain its structural integrity during composite synthesis and processing, and (3) to establish a 0008-6223/$ -see front matter Published by Elsevier Ltd. http://dx.doi.org/10.1016/j.carbon.2013.07.001 suitable matrix-reinforcement agent interface [1][2][3][4][5][6]. The strength of a MMC can be further enhanced by reducing the crystal size of the metal matrix to the lower nanoscale [7].…”
Section: Introductionmentioning
confidence: 99%